Berwirausaha Ikan Lele Menjadi Produk Bernilai Guna Peningkatan Pendapatan Petani Di Kelurahan Koya Koso Abepura - Westim Ratang; Mery Pigome (UNIVERSITAS CENDERAWASIH, 2022)
Koya Koso is one of the areas located in Jayapura City which have a potential agricultural products in the form of vegetables, fruit and freshwater fish cultivation, namely catfish. One of the agricultural products found in that area is catfish which is only sold in unprocessed form. The purpose of this activity is to develop the catfish business into a value added that will increase the income of farmers in Koya Koso Abepura. Beside that, to improve the skills in processing catfish into products that are ready for sale and management knowledge to farmers in Koya Koso, Abepura. This activity held in the garden owned by farmers who generally raise catfish, Mujair, Gastor fish and also gardening a corn, kale, mustard greens and others. Preparations are made by gathering the farmers who is attend this activity such as a mothers, teenagers and fathers who were working. The interviewer for this activity is Lidya Chandra, who is an entrepreneur in making catfish floss. The results of this community service related to the topic of shredded catfish training showed that there is an impact of training on making catfish floss for farmers who did not know how to manage itu in the first and wanted to try entrepreneurship in order to increase their family income and the business of farmers in Koya Koso.